Transplanted Embryonic Neurons Improve Functional Recovery by Increasing Activity in Injured Cortical Circuits. (8th April 2020) - Andreoli, Evgenia; Petrenko, Volodymyr; Constanthin, Paul Eugène; Contestabile, Alessandro; Bocchi, Riccardo; Egervari, Kristof; Quairiaux, Charles; Salmon, Patrick; Kiss, Jozsef Zoltan
Abstract: Transplantation of appropriate neuronal precursors after injury is a promising strategy to reconstruct cortical circuits, but the efficiency of these approaches remains limited. Here, we applied targeted apoptosis to selectively ablate layer II/III pyramidal neurons in the rat juvenile cerebral cortex and attempted to replace lost neurons with their appropriate embryonic precursors by transplantation. We demonstrate that grafted precursors do not migrate to replace lost neurons but form vascularized clusters establishing reciprocal synaptic contacts with host networks and show functional integration. These heterotopic neuronal clusters significantly enhance the activity of the host circuits without causing epileptic seizures and attenuate the apoptotic injury-induced functional deficits in electrophysiological and behavioral tests. Chemogenetic activation of grafted neurons further improved functional recovery, and the persistence of the graft was necessary for maintaining restored functions in adult animals. Thus, implanting neuronal precursors capable to form synaptically integrated neuronal clusters combined with activation-based approaches represents a useful strategy for helping long-term functional recovery following brain injury.